Study to Compare Anxiety, Depression and Alcohol Use between Manhole Workers and Other Class Four Municipality Workers (Medico Legal Update, 2021)
Background: Working conditions has serious effect on person’s mental and physical health. Manholeworkers work in very demanding and inhuman environment. Many studies shown prevalence of depression,anxiety and substance abuse in people involved in manual cleaning work.Methodology: Total 100 class IV workers from which 50 manhole workers and rest 50 were other classIV, were studied in a single centric cross-sectional study. The scales used were AUDIT, HAM-A, HAM-D.Statistical Analysis: Scores obtained were computed using basic descriptive statistics as well as computerizedstatistical software.Results: Compared to other class IV workers, more numbers of manhole workers were having significantand more severe anxiety, depression and substance abuse.Conclusions: This study provides insight about mental health of somewhat neglected class of societies.